2017
DOI: 10.1016/j.physa.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of risk and bailout strategy in banking systems

Abstract: In this paper we analyse the long-term costs and benefits of bailout strategies in models of networked banking systems. Unlike much of the current literature on financial contagion that focuses on systemic risk at one point in time, we consider adaptive banks that adjust risk taking in response to internal system dynamics and regulatory intervention, allowing us to analyse the potentially crucial moral hazard aspect associated with frequent bailouts. We demonstrate that whereas bailout generally serves as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…De Caux, McGroarty and Brede (2017) analyzed the long-term costs and benefits of bailout strategies in banking systems. They found that bailouts serve as effective tools that limit the occurrence of bank failures in the short-run.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…De Caux, McGroarty and Brede (2017) analyzed the long-term costs and benefits of bailout strategies in banking systems. They found that bailouts serve as effective tools that limit the occurrence of bank failures in the short-run.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Governments worldwide have launched an extraordinary assisted measures for banks in developed economy Rose and Wieladek (2012), De-Caux et al (2017), and emerging economy (Shehu et al, 2014). In recent time, the authorities all over the world designated for supervision and regulating the banking sector have resolved to a different rescue measures such as extended liquidity support, nationalization of banks, capital injection and blanket guarantees (Bayazitova & Shivdasani, 2012;Duchin & Sosyura, 2014;Berger et al, 2016).…”
Section: The Relationship Between Intervention and Bank's Performancementioning
confidence: 99%
“…Acharya et al (2015) analyze how the capital requirements can address moral hazard problems in banking associated risk shifting and managerial under-provision of effort in loan monitoring. A number of studies (Antzoulatos and Tsoumas, 2014;Cheng et al, 2016;De Caux et al, 2017;Janda, 2009;Mariathasan et al, 2014) points to the evidences of moral hazard behavior of financial institutions in case of various forms of government support i.e. bailout, guarantees, deposit insurance, etc.…”
Section: Introductionmentioning
confidence: 99%